Chemical Constituents and Antioxidant Activity of Teucrium barbeyanum Aschers - A. Alwahsh, Mohamed Ali; Khairuddean, Melati; Wong, Keng Chong (ACG Publications, 2015)
The different extracts of the aerial parts of Teucrium barbeyanum Aschers. were investigated for the chemical constituents and antioxidant activities. The chemical investigation of the plant led to the isolation of eleven known compounds through column chromatography in which nine were flavonoids and the other two were simple phenolic compounds. The compounds were characterized using NMR techniques (1H, 13C, DEPT- 135 and 90, COSY, HMQC, HMBC and NOESY), UV spectroscopy and EI/ESI spectrometry. The isolated compounds were identified as 5-hydroxy-3,6,7,4-tetramethoxyflavone (1), salvigenin (2), 5-hydroxy-6,7,3,4- tetramethoxyflavone (3), chrysosplenetin (4), cirsilineol (5), cirsimaritin (6), cirsiliol (7), apigenin (8) and luteolin (9), in addition to methyl caffeate (10) and 4-hydroxybenzoic acid (11). The antioxidant activity of the extracts was evaluated using 2,2-Diphenyl-1-picrylhydrazyl (DPPH), 2,2-Azino-bis(3-ethylbenzothiazoline-6- sulfonic acid) diammonium salt (ABTS) and ferric reducing antioxidant power (FRAP) methods. Ethyl acetate and butanol extracts showed comparable antioxidant activity to known antioxidants; trolox and ascorbic acid and the highest total phenolic and flavonoid contents. The active components were extracted efficiently in 70% aqueous methanol after defatting procedure. This is the first time the aforementioned compounds are isolated from this plant, and there has been no previous report on the biological studies on this species.